2005
DOI: 10.1007/s00204-005-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative stress and inhibition of plasminogen activator inhibitor-1 production in endothelial cells following exposure to organic extracts of diesel exhaust particles and urban fine particles

Abstract: Endothelial cells play important roles in anticoagulant and fibrinolytic systems. Recent studies suggest that increases in ambient particulate matter (PM) levels have been associated with an increase in mortality rate from cardiovascular diseases. We examined the production of heme oxygenase-1 (HO-1) and factors related to the fibrinolytic function by rat heart microvessel endothelial cells exposed to organic extracts of diesel exhaust particles (OE-DEP) and urban fine particles (OE-UFP) to investigate the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…Inhalation of particles produces oxidative stress directly or via acute pulmonary inflammation, thus causing a series of events, such as the production of proinflammatory mediators, an increase of extracellular calcium influx, and the disruption of nitric oxide regulation (Stone et al 2000; Thomas et al 2001), that may impair autonomic function and hence HRV. Diesel particles have also been shown to increase oxidative stress in endothelial tissue, inducing the production of HMOX-1 (Furuyama et al 2006). The viability of cell cultures of microvascular endothelial cells was impaired by diesel particles with an accompanying large increase in induction of HMOX-1 (Hirano et al 2003); this process was blunted by N -acetylcysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of particles produces oxidative stress directly or via acute pulmonary inflammation, thus causing a series of events, such as the production of proinflammatory mediators, an increase of extracellular calcium influx, and the disruption of nitric oxide regulation (Stone et al 2000; Thomas et al 2001), that may impair autonomic function and hence HRV. Diesel particles have also been shown to increase oxidative stress in endothelial tissue, inducing the production of HMOX-1 (Furuyama et al 2006). The viability of cell cultures of microvascular endothelial cells was impaired by diesel particles with an accompanying large increase in induction of HMOX-1 (Hirano et al 2003); this process was blunted by N -acetylcysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induction by urban fine particles has been discussed as a possible risk factor for cardiovascular diseases [75]. Recently, also diisocyanates, fluoride, N-nitrosofenfluramine, and the frequently used non-steroidal anti-inflammatory drug indomethacin have been reported to cause oxidative stress-mediated toxicity.…”
Section: Oxidative Stress In Cellsmentioning
confidence: 99%
“…18,27 TGF-b can also prevent the degradation of collagen via increased PAI-1 expression. 17,28 It has been reported that ROS modulate fibroblast proliferation and their transition into matrix-producing myofibroblasts in the heart. 5,29 Furthermore, ROS induce expression of TGF-b1 and type I collagen, and lead to activation of TGF-b from its latent form.…”
Section: Cardioprotection By Kallistatin Via Antioxidation L Gao Et Almentioning
confidence: 99%